2016
DOI: 10.18632/oncotarget.8262
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence characteristics of high-risk human papillomaviruses in women living in Shanghai with cervical precancerous lesions and cancer

Abstract: A complete understanding of the natural history of infection with high-risk human papillomaviruses (HPVs) in cervical cancer requires data from regional and ethnic studies. The prevalence of high-risk HPVs was evaluated retrospectively in 2040 patients with cervicitis, 239 with cervical intraepithelial neoplasia grade 1 (CIN1), 242 with CIN2/3, and 42 patients with invasive squamous cell carcinoma (SCC) based on data from patients who visited our hospital between May 2013 and May 2015. The rates of high-risk H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…In present study, HPV 58 is a dominant high-risk genotype and the prevalence of HPV58 in patients with cervicitis, CIN I, CIN II/III and invasive SCC was 9.09%, 21.28%, 25.40 and 20.49%, respectively. Although the overall prevalence rate of HPV58 in our research is very higher than the reports of Japanese and world, in which HPV58 prevalence rates are 7.0% in patients with CIN II/III and 3.3% ~ 13.3% in patients with SCC [10, 37], our result is consistent with some recent Chinese reports [33, 38], where 16.4%, 20.1%, 23.5% and 31.4% patients with cervicitis, CIN I, CIN II/III and invasive SCC and 29.1% and 24.3% patients with CIN II/III and invasive SCC showed HPV58 infection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In present study, HPV 58 is a dominant high-risk genotype and the prevalence of HPV58 in patients with cervicitis, CIN I, CIN II/III and invasive SCC was 9.09%, 21.28%, 25.40 and 20.49%, respectively. Although the overall prevalence rate of HPV58 in our research is very higher than the reports of Japanese and world, in which HPV58 prevalence rates are 7.0% in patients with CIN II/III and 3.3% ~ 13.3% in patients with SCC [10, 37], our result is consistent with some recent Chinese reports [33, 38], where 16.4%, 20.1%, 23.5% and 31.4% patients with cervicitis, CIN I, CIN II/III and invasive SCC and 29.1% and 24.3% patients with CIN II/III and invasive SCC showed HPV58 infection.…”
Section: Discussionsupporting
confidence: 89%
“…The distribution of dominant HPV genotypes showed obvious regional differences [33]. HPV18 is reported to be one of the two most carcinogenic HPV genotypes (HPV16 and 18), accounting for 10 ~ 15% of cervical cancers [11, 24, 32].…”
Section: Discussionmentioning
confidence: 99%
“…In our population, the HPV 18 prevalence rates in patients with cervicitis, CIN1, CIN2‐3 and invasive SCC were 11.6%, 10.9%, 8.3%, and 11.8%, respectively. Because the patients in the study were at high risk of cervical cancer and received colposcopies due to abnormal cervical screening results, the infection rates among patients with cervicitis and CIN1 were relatively higher than those in other reports . Another reason was that as many as 66.6% (513/770) of the patients with cervicitis and 62.0% of the patients (245/395) with CIN1 received a colposcopy and cervical biopsy due to slight abnormalities, which included simple HPV 16/18‐positive patients and HPV‐positive ASC‐US.…”
Section: Discussionmentioning
confidence: 54%
“…Because the patients in the study were at high risk of cervical cancer and received colposcopies due to abnormal cervical screening results, the infection rates among patients with cervicitis and CIN1 were relatively higher than those in other reports. 46 Another reason was that as many as 66.6% ( Asia. 47 In our study, the HPV 52 prevalence rates in patients with cervicitis, CIN1, CIN2-3, and invasive SCC were 15.2%, 14.4%, 16.8%, and 3.9%, respectively.…”
Section: Ors For Hpv 16 Infectionsmentioning
confidence: 99%
“…It has been found in 11.5 to 28% of cervical cancer patients in China, 16% in Korea and 8% in Japan [15]. In a recent study that evaluated the prevalence of high-risk HPVs in cervical intraepithelial lesions in Shanghai showed that the three most dominant HPV genotypes were HPV16, 58, and 52 [16]. HPV58 is the third most common HPV type in Eastern Asia overall [17].…”
Section: Discussionmentioning
confidence: 99%